Sensorfusion zur Kompensation von Messfehlern bei kamerabasierter Farbverteilungsmessung - Sayanca, Inca Leopoldo (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2018)
In this work we introduce a colour measurement method based on sensor fusion for the complete characterization of LED lighting systems. The measurement information from indirect, high-resolution filter camera measurements is combined with spectral and photometric point measurements. The results of the developed measurement method are angle-resolved chromaticity coordinates as well as angle-resolved spectral information.